2015
DOI: 10.1123/jpah.2013-0487
|View full text |Cite
|
Sign up to set email alerts
|

Walking Workstation Use Reduces Ambulatory Blood Pressure in Adults with Prehypertension

Abstract: Background:The acute effect of low-intensity walking on blood pressure (BP) is unclear. Purpose: To determine if the acute use of a walking workstation reduces ambulatory blood pressure (ABP) in prehypertensive men and women. Methods: Ten prehypertensive adults participated in a randomized, cross-over study that included a control workday and a walking workstation workday. ABP was measured for 7 hour during the workday and for 6 hour after work. Results: Both systolic BP (SBP) (134 ± 14 vs. 137 ± 16 mmHg; P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
3
17
1
Order By: Relevance
“…Several randomized trials employing cross-over study designs have consistently shown clinically meaningful acute improvements in postprandial glucose metabolism following the initiation of frequent (every 20–30 min) short (2–3 min) interruptions during prolonged sitting involving either light-intensity or moderate-intensity ambulation, standing, or simple resistance activities (3). Some have also demonstrated improved responses in blood pressure (23, 44, 79, 80), lipid metabolism (22, 26, 33), hemostatic markers (34) and endothelial function (63, 73). In a recent meta-analysis of experimental studies, Chastin et al (15) confirmed beneficial effects on glycemic control with interruptions in sitting involving both light-intensity physical activity and moderate-vigorous intensity physical activity.…”
Section: Observational Epidemiologic Studies Linking Sedentary Behavimentioning
confidence: 99%
“…Several randomized trials employing cross-over study designs have consistently shown clinically meaningful acute improvements in postprandial glucose metabolism following the initiation of frequent (every 20–30 min) short (2–3 min) interruptions during prolonged sitting involving either light-intensity or moderate-intensity ambulation, standing, or simple resistance activities (3). Some have also demonstrated improved responses in blood pressure (23, 44, 79, 80), lipid metabolism (22, 26, 33), hemostatic markers (34) and endothelial function (63, 73). In a recent meta-analysis of experimental studies, Chastin et al (15) confirmed beneficial effects on glycemic control with interruptions in sitting involving both light-intensity physical activity and moderate-vigorous intensity physical activity.…”
Section: Observational Epidemiologic Studies Linking Sedentary Behavimentioning
confidence: 99%
“…In light of such evidence, an expert statement on reducing prolonged periods of sedentary work recommended that desk-based employees should initially accumulate a minimum of 2 h/day of light-intensity activity (standing or light walking) during working hours (Buckley et al, 2015). There is currently limited research evaluating the effects of accumulating ≥2 h of lightintensity walking over a single work day on postprandial cardiometabolic risk (Zeigler, Mullane, Crespo, Buman, & Gaesser, 2016;Zeigler, Swan, Bhammar, & Gaesser, 2015) and none of these studies have examined glucose, insulin, or triglyceride responses. Furthermore, there is limited understanding regarding the influence of sex on cardiometabolic responses to interrupting sedentary time (Dempsey et al, 2016a;Dunstan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, Reed et al [28] evaluated the effects of the interventions that included counselling, fitness testing, messages and email prompts, diet and health promotion on working-age woman whereas this meta-analysis reports the effects of cycle and treadmill desks on sedentary workers. Two studies included in this meta-analysis [37,38] focused primarily on the effects of cycle and treadmill desk interventions on blood pressure compared to a seated condition. In a study by Zeigler et al [37], subjects with prehypertension were included (prehypertension was defined as mean systolic blood pressure of 120-139 mmHg and mean diastolic blood pressure of 80-90 mmHg).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies included in this meta-analysis [37,38] focused primarily on the effects of cycle and treadmill desk interventions on blood pressure compared to a seated condition. In a study by Zeigler et al [37], subjects with prehypertension were included (prehypertension was defined as mean systolic blood pressure of 120-139 mmHg and mean diastolic blood pressure of 80-90 mmHg). Similarly, in another study by Zeigler et al [38], the inclusion criteria were prehypertension and BMI > 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation